THEME CONTEMPORARY APPROACHES IN TEACHING FOREIGN LANGUAGES TO SECONDARY SCHOOL STUDENTS - Umaraliyeva Munojat Mashrabovna; Teshaboyeva Muxlisabonu Ma'rufjon qizi (Journal of new century innovations, 2023)
Annotation: This article is about modern methods of teaching grammar to secondary school students . It compares two approaches , namely deductive and deductive ways of teching and analyzes its effects on the language acquisition of students.